The role of Islamic Governance on Islamic social reporting disclosure of Indonesia Islamic Banks - Wiji Astuti; Ahmad Nurkhin (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
The aim of this study is to analysis the effect of profitability, leverage, and investment account holders on Islamic social reporting disclosure that moderate by Islamic corporate governance. The subjects of the study are sharia banks in Indonesia during a period of 2010-2017. By employing purposive sampling, there are 8 sharia banks as research samples and 64 analysis units. The data was analyzed by using SEM-PLS. The result showed that profitability and leverage have no effect on the Islamic Social Reporting Disclosure and Islamic Corporate Governance cannot moderate the effect of profitability and investment account holders on the Islamic social reporting disclosure